Modelling and simulation of the train brake system in low adhesion conditions. (March 2020) - Alturbeh, Hamid; Stow, Julian; Tucker, Gareth; Lawton, Alan
This paper describes the current version of the Low Adhesion Braking Dynamic Optimisation for Rolling Stock (LABRADOR) simulation tool that can predict the train brake system performance and support decision-making in the design and optimisation of the braking system including wheel slide protection, sanders and the blending and control of friction and dynamic brakes in low adhesion conditions. The model has been developed in MATLAB/Simulink and is intended to mimic the braking performance of both older and newer generations of multiple unit passenger trains. LABRADOR models have been initially validated by comparing simulation results for a single car train (Class 153) and two-car train (Class 158) in dry conditions with experimental tests, for tare and crush laden vehicles. This project is supported by RSSB and a technical steering group composed of railway braking experts, suppliers and train operators and manufacturers.